Hiperplasia linfoide del yeyuno. Nuestra experiencia. - Sagaró González, Eduardo; Ruíz Méndez, Alberto; Fragoso Arbelo, Trini; Grá Oramas, Bienvenido; Castañeda Guillot, Carlos (Revista Cubana de Pediatría, 2025)
Se presenta la experiencia en el Instituto de Gastroenterología.